Teologi Peristiwa Sabda - E.P.D. Martasudjita (Jurnal Orientasi Baru, 2007)
The significance of the Word of God in the life of the Church is taken for granted. The Second Vatican Council empasized its central role in the life of the people of God (DV 21). The problem is that many Catholics prefer the sacramental celebrations and many other popular devotions. At the same time, a good number of their leaders have difficulties in preaching the Word of God and to make it relevant to the struggle of the people of today. Therefore a good discussion on the richness of the Word of God is extraordinarily important. This article views the Word of God primarily as an "event" Biblical, systematic, liturgical, pastoral and ecumenical approaches are employed to discuss different dimensions of the Word of God as an event of a communication between God and the people of God.